Credit rationing, output gap, and business cycles - Frédéric Boissay (European Central Bank (ECB), 2001)
The cost-of-financing channel version of the financial accelerator proposed by Bernanke & Gertler [1989] is prominent in the literature. Yet, this particular channel has not been validated by empirical work. This paper presents an alternative version of the accelerator. This new accelerator, based on quantity credit rationing, is shown to be more powerful than the traditional accelerator. By causing factor under-utilization credit rationing generates an output gap persistent and sensitive to technology shocks. This accelerator is not a substitute to the traditional mechanism though, but rather a complement. My model helps improve the understanding of financial transmission mechanisms. It considers several types of collaterals. Financial frictions generate persistence when collaterals take the form of tangible assets. They generate amplification when collaterals take the form of cash flows or when asset prices are variable.
Keywords: E32; E44; 330